Home industry entrepreneurship empowerment: LINSU production to support the economy of families around campus - Indah Adelina Siregar; Safrizal; Indah Kartika Sandra (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2025)
This Community Service Program (PKM) was conducted around the campus of Universitas Satya Terra Bhinneka with the aim of enhancing community skills in producing and marketing dishwashing liquid as a home industry. The activity began with a pre-test to assess participants’ initial understanding of the production process, packaging, and marketing strategies. The pre-test results showed that most participants had no prior experience in soap making and limited knowledge of packaging and product marketing. The training included a live demonstration of the soap-making process, followed by sessions on product packaging and marketing strategies, particularly through the use of social media. Post-training evaluation showed significant improvements: 90.32 percent of participants understood the soap-making process, 100 percent grasped proper packaging techniques, and 74.19 percent understood how to utilize digital marketing strategies. Interest in starting a dishwashing liquid business increased from 29.03 percent to 77.42 percent after the training. This program effectively provided practical and applicable skills, promoted economic self-reliance, and strengthened the synergy between the university and the community in developing local potential. The training is expected to stimulate the emergence of new, sustainable, and competitive household-based business units in the local market.